Preservation Rhinoplasty: Evolution and Current State of Practice in the United States - Patel, Priyesh N.; Friedman, Oren; Kandathil, Cherian K.; Most, Sam P. (Facial Plastic Surgery, 2021)
Classic Joseph hump reduction techniques have been a hallmark of current rhinoplasty practice and teaching. Recently, there has been a renewed global interest in preservation rhinoplasty techniques, although these techniques are not new. The work and techniques of innovative surgeons including Goodale, Lothrop, and Cottle describing preservation concepts from the late nineteenth century and early twentieth century were not as prevalently adopted as open structural approaches. As such, there has been a relative paucity in both research and teaching of preservation techniques—particularly in the United States. A survey of members of the American Academy of Facial Plastic and Reconstructive Surgery and The Rhinoplasty Society (145 respondents) demonstrates that while 15 (10%) of surgeons are not at all familiar with dorsal preservation surgery, 130 (90%) were. In the group that was familiar with dorsal preservation, the majority were only somewhat familiar (84, 65%) with these techniques. Only 11 respondents received any formal training in dorsal preservation techniques during residency or fellowship. 61 (42%) had attended a course or conference in which dorsal preservation techniques were discussed. One-hundred twenty-two survey respondents (84.1%) do not currently implement preservation techniques into their rhinoplasty practice. Twelve (8%) respondents implement it in <25% of cases, 5 (3%) in 25 to 50% of cases, and 6 (4%) in >50% of cases. As research and formal training in preservation rhinoplasty grow, familiarity and implementation of these techniques will likely also grow in the United States.
Keywords: preservation rhinoplasty; dorsal preservation; rhinoplasty